-h-10=h+6

Simple and best practice solution for -h-10=h+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -h-10=h+6 equation:


Simplifying
-1h + -10 = h + 6

Reorder the terms:
-10 + -1h = h + 6

Reorder the terms:
-10 + -1h = 6 + h

Solving
-10 + -1h = 6 + h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1h' to each side of the equation.
-10 + -1h + -1h = 6 + h + -1h

Combine like terms: -1h + -1h = -2h
-10 + -2h = 6 + h + -1h

Combine like terms: h + -1h = 0
-10 + -2h = 6 + 0
-10 + -2h = 6

Add '10' to each side of the equation.
-10 + 10 + -2h = 6 + 10

Combine like terms: -10 + 10 = 0
0 + -2h = 6 + 10
-2h = 6 + 10

Combine like terms: 6 + 10 = 16
-2h = 16

Divide each side by '-2'.
h = -8

Simplifying
h = -8

See similar equations:

| 24.33333333+-2.333333333y+4x+23=180 | | 4(5(-8)+4)=9((-8)-8) | | -10+2y=8+4y | | 7(y+1)=6y-9 | | Ht=-16t^2+35+ho | | -8t=-3-5t | | 18y-405=99 | | 10-b=9b-10 | | 4c-2=8c-10 | | 2+8=-5(6x-2) | | -p=-7-2p | | 9x-38+21y-1=180 | | 3x+-5=7x+7 | | 8+g=-10-2g | | 24+0.20x=x | | 19=(x/8) | | 2r=7+3r | | 2x+14=3x-11 | | 2v-3-11v=-6(1+19v)+-6(-18v-11) | | -8d=8-6d | | 3n=2+5n | | 5x+14=4x | | C=37.03+0.25x | | 5k=-6+6k | | 3(m-15)=m-7 | | -q-10=-2q | | x+80+50+x+60=180 | | 28+5=44 | | 22=n-(-4) | | 7x+7(2x-9)=63 | | g(x)=3x^2+9x | | 6y-9=7 |

Equations solver categories